The AI Revolution in Mobile App Development : Transforming Workflows and Elevating Performance - Aditya Undirwadkar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Artificial intelligence has fundamentally transformed how mobile applications are conceptualized, developed, and maintained. This paradigm shift has redefined industry standards by streamlining development workflows, enhancing code quality, revolutionizing testing methodologies, optimizing resource utilization, strengthening security postures, and facilitating global reach through advanced localization. AI-powered tools generate substantial portions of code, detect subtle bugs, create comprehensive test suites, identify optimization opportunities, scan for security vulnerabilities, and enable efficient adaptation for diverse markets. These capabilities allow developers to focus on higher-value activities while delivering more reliable, efficient, and user-centric applications. The democratization effect of AI integration has enabled smaller teams to compete effectively with larger organizations, broadening market participation and innovation. As AI systems become increasingly sophisticated, their integration throughout the mobile development lifecycle represents not merely an improvement in existing practices but a complete reimagining of how applications are built and sustained in the global marketplace.
Keywords: Artificial Intelligence; Mobile Application Development; Code Generation; Automated Testing; Resource Optimization; Security Enhancement; Localization